Grover disease and bullous pemphigoid: a clinicopathological study of six cases. (27th September 2018) - Ellenbogen, E.; Geller, S.; Azrielant, S.; Zeeli, T.; Goldberg, I.; Schmidt, E.; Zillikens, D.; Mrowietz, U.; Sherman, S.; Mercer, S.; Didkovsky, E.; Hodak, E.; et al.
Summary: Grover disease (GD) is an idiopathic dermatosis that typically manifests as itchy papules over the trunk in middle‐aged men. Bullous pemphigoid (BP) is an autoimmune bullous disease that affects older people. Not only are the two diseases easily distinguishable on clinical grounds, they are also characterized by differences in histopathology, pathogenesis and response to treatment Thus, the co‐occurrence of these two conditions in the same patient is usually considered coincidental. In this report, we present a multicentre retrospective analysis of six patients who developed both GD and BP over a short period of time, and in all cases but one, GD preceded BP. We discuss the clinical and histopathological features of these patients, and the suggested mechanisms of the diseases. We conclude that GD might predispose to the development of BP.